Demographic Features in the Planning Decision of the Old City Mahalla - Talipov, M.A.; Tulkunov, O. A. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article outlines the influence of natural-climatic, socio-economic and demographic factors on the formation of the architectural and planning solution of the Old City. The issues of transformation of housing depending on the gender and age composition of the population are highlighted. The traditions of folk architecture associated with the above factors are considered.